Determination of Phthalate Plasticisers in Palm Oil Using Online Solid Phase Extraction-Liquid Chromatography (SPE-LC) - Nazarudin Ibrahim; Rozita Osman; Azmui Abdullah; Norashikin Saim (Journal of Chemistry)
Contamination of phthalates plasticisers to food has raised concern as some of the phthalates are suspected to be endocrine disruptors. The phthalates have high affinity with oily environment and analysing these chemicals in such matrices is difficult because of the trace amount of the analyte and interference from matrix. An online solid phase extraction (SPE) technique using a large volume (3.5 mL) injection was developed for the analysis of 6 common plasticisers in palm oil. A simple sample preparation involving alumina as a fat retainer and methanol : acetonitrile (1 : 1) as the extraction solvent was performed prior to the usage of online SPE-LC system. This system consists of two columns, C16 for the solid phase extraction (SPE) and C18 as the analytical column, and a photo diode array detector. The calibration curves were linear from 5 to 1000 μg L−1, with correlation coefficients above 0.99. The instrumental limit of detection was 3 μg L−1 and satisfactory recovery was obtained. A screening on a few samples in the retail market revealed the presence of dibutyl phthalate (DBP) and butylbenzylphthalate (BBP) in the palm oil, with concentration less than 1 mg L−1.